Unexpected curative effect of PD-1 inhibitor in gastric cancer with brain metastasis: A case report - Wang, Qijun; Shen, Zhewei; Ge, Mengxi; Xu, Jie; Zhang, Xin; Zhu, Wei; Liu, Jie; Hua, Wei; Mao, Ying (Frontiers in Oncology, 2023)
Background: Gastric cancer (GC) is the third most common cause of cancer-related death in the world. Several clinical trials have proven that the use of PD-1/PD-L1 inhibitors can improve the survival of late-stage GC patients and is suggested in NCCN and CSCO guidelines. However, the correlation between PD-L1 expressions and the response to PD-1/PD-L1 inhibitors is still controversial. GC rarely develops brain metastasis (BrM) and currently there is no therapeutic protocol for GC BrMs. Case Presentation: We report a case where a 46-year-old male suffering from GC with PD-L1 negative BrMs 12 years after GC resection and 5 cycles of chemotherapy. We treated the patient with the immune checkpoint inhibitor (ICI) Pembrolizumab and all metastatic tumors achieved a complete response (CR). A durable remission of the tumors is confirmed after 4 years of follow-up. Conclusion: We shared a rare case with PD-L1 negative GC BrM responding to PD-1/PD-L1 inhibitors, the mechanism of which is still unclear. The protocol of therapeutic choice for late-stage GC with BrM is urgently needed. And we are expecting biomarkers other than PD-L1 expressions to predict the efficacy of ICI treatment.